العلم والاخلاق..جدل الثورة العلمیة والمستقبل - د. كوثر عباس الربیعي (مجلة كلية التربية للبنات, 2019)
The world is currently standing on a huge ethical crossroad because of the scientific progress that produced many conclusions and removed the barricades between humans , now it is extremely easy to reach everywhere thanks to the communications' revolution , and now it is common to speak of things that were prohibited until recently. This duality is clear in the meanings of words used in different languages spoken by the different nations of the world...Especially those that reflect the fundamentals of human existence like the words: ethics, conscience, culture and love, war and peace, interests, terrorism and others. One can also see the controversial relation between science and ethics starting from the truth that ethics have since emergence been connected to the mind's activity of differentiating between good and evil, and in the mind lies the ability of scientific innovations…Through the ages, science and ethics walked side by side each effecting the other, and the formation of society including the relations that are based on cooperation or competition, love or hatred and so on is the ground in which we exercise the building and evolution process which is based on the reconciliation of science and ethics.